Sharing Knowledge on Basic General and Electrical Occupational Health and Safety for State of Vocational High School (SMK) 2 Bogor Students - Pawenary; Muniroh; Suwandi, Arief; Savitri, Fitri; Larasati, Ayu (Jurnal Locus Penelitian dan Pengabdian, 2026)
In this section, you describe the major challenges facing education in Indonesia, particularly in Vocational High Schools (SMK). You mention the existing problem, namely students' lack of understanding of the basics of Occupational Health and Safety (OHS), particularly electrical safety. This has the potential to lead to a high risk of workplace accidents and equipment damage during practical work or internships. The research objective in this abstract is to describe the purpose of the Community Service Program (PKM) conducted by lecturers and students of Esa Unggul University. The main focus is to improve students' understanding of general OHS and electrical safety at SMK Negeri 2 Bogor City through interactive training and hands-on practice. This section explained how the PKM program is implemented, namely by providing interactive training that includes material delivery, case study simulations, the use of OHS checklists, standard operating procedures (SOPs) for electrical practice, and demonstrations on the correct use and maintenance of equipment. The methods used are applicative, aiming to directly involve students in learning and practical training. The results of this program indicate an increase in students' knowledge and awareness regarding OHS aspects, particularly in the context of electrical safety. Furthermore, the program successfully strengthened students' practical skills, better preparing them for entering the workforce. This section concludes that the PKM activities not only benefited students who gained new knowledge and skills, but also benefited Esa Unggul University by introducing the institution to students and the school community. These activities also enabled the university to contribute to community service.